TECHNOLOGY READINESS: WHAT ARE THE CATALYSTS? - Prakoso, Albrian Fiky; RoziqiFath, Zain Fuadi Muhammad; Ginanjar, Ardhita Eko; Wulandari, Wida; Kamalia, Putri Ulfa; Irawan, Nico (Universitas Labuhanbatu, 2025)
Purpose- This study aims to (1) analyze the influence of university readiness on technology readiness, mediated by the readiness of prospective economics teachers, and (2) identify key socio-institutional factors affecting the technological preparedness of future educators in Indonesia.Methodology- Data were collected via an online survey of 400 economics education students across East Java, Indonesia universities. Structural Equation Modelling (SEM) using SmartPLS 3.0 was employed to test hypotheses and evaluate the mediating role of prospective teachers' readiness.Findings— University readiness, directly and indirectly, enhances technology readiness by mediating perspective teachers' preparedness (β = 0.48, p < 0.001). However, disparities in technological readiness among participants were linked to contextual factors such as family environment (21% variance), financial constraints (18%), and institutional culture (35%). Universities emerged as pivotal actors, contributing 62% to developing prospective teachers' technological competencies.Cortribution– The findings underscore the critical role of higher education institutions in designing targeted interventions to bridge socio-institutional gaps and strengthen technological readiness. Recommendations include curriculum reforms integrating adaptive training modules and collaborative policies addressing financial and cultural barriers. This study provides a framework for fostering equitable and sustainable technology integration in economics teacher education programs.